PEMANFAATAN VIDEO NARATIF BERBASIS AI SEBAGAI MEDIA REMEDIAL PADA MATA PELAJARAN SKI KELAS XI MADRASAH ALIYAH - Rahmani, Ady fauzi (Prosiding Temu Ilmiah Nasional Guru, 2026)
This study aims to evaluate the use of AI-based narrative video as a remote remedial learning medium for the Islamic Cultural History (SKI) subject in Grade XI of Madrasah Aliyah. The instructional video was created using AIStudios.com, a platform that enables the development of educational narratives with virtual presenters and automated visuals. The video content focuses on the thoughts of three Islamic reformers: Jamaluddin Al-Afghani, Muhammad Abduh, and Muhammad Rasyid Rida. After watching the two-minute video, students completed a short quiz consisting of five multiple-choice questions and responded to a Likert-scale perception questionnaire. The results indicate that the average student mastery reached 92%, with most respondents scoring highly on the quiz. On the perception survey, students gave consistently positive responses, particularly regarding the video’s clarity (average score: 4.4) and its ability to support independent review (average score: 4.4). The lowest-rated aspect, though still relatively high, was students’ understanding of the reformist figures (average score: 3.8). These findings provide early evidence that AI-based narrative video media holds significant potential as an effective and efficient alternative for remedial learning, particularly suited to the needs of the digital-native generation